Influence of Support Type and Metal Loading in Methane Decomposition over Iron Catalyst for Hydrogen Production. Issue 7 (8th July 2015) - Ibrahim, Ahmed A.; Al‐Fatesh, Ahmed S.; Khan, Wasim U.; Soliman, Mostafa A.; AL Otaibi, Raja L.; Fakeeha, Anis H.
Abstract Natural gas resources, stimulate the method of catalytic methane decomposition. Hydrogen is a superb energy carrier and integral component of the present energy systems, while carbon nanotubes exhibit remarkable chemical and physical properties. The reaction was run at 700 °C in a fixed bed reactor. Catalyst calcination and reduction were done at 500 °C. MgO, TiO2 and Al2O3 supported catalysts were prepared using a co‐precipitation method. Catalysts of different iron loadings were characterized with BET, TGA, XRD, H2‐TPR and TEM. The catalyst characterization revealed the formation of multi‐walled nanotubes. Alternatively, time on stream tests of supported catalyst at 700 °C revealed the relative profiles of methane conversions increased as the %Fe loading was increased. Higher %Fe loadings decreased surface area of the catalyst. Iron catalyst supported with Al2O3 exhibited somewhat higher catalytic activity compared with MgO and TiO2 supported catalysts when above 35% Fe loading was used. CH4 conversion of 69% was obtained utilizing 60% Fe/Al2O3 catalyst. Alternatively, Fe/MgO catalysts gave the highest initial conversions when iron loading below 30% was employed. Indeed, catalysts with 15% Fe/MgO gave 63% conversion and good stability for 1 h time on stream. Inappropriateness of Fe/TiO2 catalysts in the catalytic methane decomposition was observed.